Comparison of the impacts of different multimodalities on incidental l2 vocabulary learning - Çekiç, Ahmet; Demirezen, Mehmet (Moderna Språk, 2020)
Multimodality of input in incidental L2 vocabulary learning has recently been a topic of interest among language acquisition researchers, yet the results have been somewhat contradictory. This study seeks to compare the impacts of two different multimodalities on incidental L2 vocabulary learning, namely, reading-plus-watching (experimental group I) vs. reading-plus-listening (experimental group II), as compared to the reading only condition, which is included as a control measure. Experimental group I watched and read the transcriptions of four news texts with electronic glosses for the target words, while experimental group II read and listened to the same news texts again with electronic glosses for the same 20 target words. Next, the two experimental groups swapped roles with a new set of four news texts glossed for another group of 20 target words. The control group only read the same eight news texts without glosses. The results suggest that reading-plus-listening can be a more conducive multimodal presentation for incidental vocabulary learning as compared to reading-plus-watching. The results also challenge the validity of some principles of the Cognitive Theory of Multimedia Learning in incidental L2 vocabulary learning, while providing supporting evidence for some other principles.